2006
DOI: 10.1210/er.2006-0020
|View full text |Cite
|
Sign up to set email alerts
|

The Hair Follicle as an Estrogen Target and Source

Abstract: For many decades, androgens have dominated endocrine research in hair growth control. Androgen metabolism and the androgen receptor currently are the key targets for systemic, pharmacological hair growth control in clinical medicine. However, it has long been known that estrogens also profoundly alter hair follicle growth and cycling by binding to locally expressed high-affinity estrogen receptors (ERs). Besides altering the transcription of genes with estrogen-responsive elements, 17␤-estradiol (E2) also modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
160
1
13

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 174 publications
(175 citation statements)
references
References 340 publications
(330 reference statements)
1
160
1
13
Order By: Relevance
“…by estrogens (Harlow and Hillier, 2002; and that estrogens are recognized key hair growth regulatory steroid hormones (Ohnemus et al 2006), the reported upregulation of Ctgf expression by murine HFeSC ( Table 1) also deserves to be carefully followed up. It is conceivable that increased Ctgf release by these SCs may contribute to condition the bulge SC niche (Cotsarelis, 2006), including its mesenchymal component, i.e.…”
Section: Pointers From Hfesc Gene Profiling Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…by estrogens (Harlow and Hillier, 2002; and that estrogens are recognized key hair growth regulatory steroid hormones (Ohnemus et al 2006), the reported upregulation of Ctgf expression by murine HFeSC ( Table 1) also deserves to be carefully followed up. It is conceivable that increased Ctgf release by these SCs may contribute to condition the bulge SC niche (Cotsarelis, 2006), including its mesenchymal component, i.e.…”
Section: Pointers From Hfesc Gene Profiling Studiesmentioning
confidence: 99%
“…for glucocorticoid, retinoid, estrogen, and vitamin D3 receptors (glucocorticoid receptor (GR), retinoic acid receptor (RAR), estrogen receptor (ER), vitamin D receptor (VDR)); and mutations in VDR and retinoid receptors can cause severe alopecia in mice and man (Chebotaev et al, 2007; Billoni et al, 1994;Ohnemus et al, 2006;Reichrath et al, 1994; Page 10 of 38 A c c e p t e d M a n u s c r i p t 10 Zouboulis et al, 2007). Even though a marked, immunohistologically prominent up-or down-regulation of these receptors has not been noted, the hair growth effects of appropriate receptor ligands, especially in mice, is impressive.…”
Section: Immunohistological Patterns Of Hair Follicle Located (Neuro-mentioning
confidence: 99%
See 3 more Smart Citations